Searching for the Mechanical Fingerprint of Pre-diabetes in T1DM: A Case Report Study - Di Giacinto, Flavio; Tartaglione, Linda; Nardini, Matteo; Mazzini, Alberto; Romanò, Sabrina; Rizzo, Gaetano Emanuele; Papi, Massimiliano; De Spirito, Marco; Pitocco, Dario; Ciasca, Gabriele (Frontiers in Bioengineering and Biotechnology, 2020)
We report the case of a 38-year-old Caucasian man enrolled in a study aimed at investigating the physical properties of red blood cells (RBCs) using advanced microscopy techniques, including Atomic Force Microscopy (AFM). At the time of his first enrolment in the study, he had normal Fasting Plasma Glucose (FPG) values, a BMI of 24.1, and no other symptoms of diabetes, including fatigue, high triglycerides, low HDL cholesterol, and altered inflammatory and corpuscular RBC indices. The subject reported no family history of diabetes, obesity, and cardiovascular diseases. Despite his apparently healthy conditions, the biomechanics of his RBCs was altered, showing increased values of stiffness and viscosity. More than one year after the mechanical measurements, the subject was admitted to the Operational Unit of Diabetology of the Policlinico Gemelli Hospital with high blood glucose and glycosylated hemoglobin (HbA1c) levels and diagnosed with type 1 diabetes (T1DM). Here, we show these data, and we discuss the hypothesis that RBC mechanical properties could be sensitive to changes occurring during the prediabetic phase of T1DM